Identity and Persistence of Laotian Diaspora via Khap Thum Luang Prabang in Ban Huay Luek Community Wiang Kaen District Chiang Rai - Kaewtapee, Sapanna; Saeng-Xuto , Virapong; Tongthaworn, Rajchukarn; Sriwichailamphan, Thanes (Community and Social Development Journal, 2021)
The objective is to study the identity and persistence of Laotian Diaspora via Khap Thum Luang Prabang in Ban Huay Luek Community Wiang Kaen District Chiang Rai. This study presents a critical analysis of the identity and persistence of the Laotian Diaspora via Khap Thum Luang Prabang, Thailand. It begins by reviewing documents and books about various types of folk music, then lands to study the music, and interview those who participate in singing. Save the recording of the show for analysis, and interpret the story, how the music is broadcast. The characteristics of the music are unique to the diaspora of Laos in Thailand. The factors that make their culture have been inherited to the present day. Although they migrated to Thailand a long time ago, the music still connects the cultures of Laos Luang Prabang and Laotian diaspora. Reflection of roots and remembrance of their homeland, they can tell their history and reflect their identity as a unique Laos Luang Prabang ethnicity. It was found to be via Khap Thum Luang Prabang of Laotian diaspora, the first and second generations are still going continuously. But in the third generation, succession began to shake and there was no successor because the third-generation sequence has no living memories of the homeland of Laos’s people.